PSVIII-28 Dietary impacts on rumen, vaginal, and uterine environments in beef heifers. (8th October 2021) - Pickett, Autumn; Cooke, Reinaldo F; Brandão, Alice; Colombo, Eduardo; Mackey, Shea; Filho, Ramiro Oliveira; de Melo, Gabriela Dalmaso; Poole, Rebecca K; Pohler, Ky G
Abstract: This experiment examined the effects of diet composition on rumen, vaginal, and uterine environments in beef heifers. Fifteen rumen-cannulated, pubertal Angus-influenced heifers were used in a replicated 3 x 3 Latin square design (28-d periods and 21-d washout intervals). Dietary treatments included (as-fed) diets based on 100% grass hay (HF), 61% grass hay + 39% corn-based concentrate (INT), or 25% grass hay + 75% corn-based concentrate (HG). Treatments were offered individually to heifers once daily at 2% of their body weight. Heifers also received 280 g/d of a mineral mix containing melengestrol acetate. Rumen, vaginal, and uterine fluid samples were collected on d 0 and 28 of each period for pH measurement. Data were analyzed using the MIXED procedure of SAS (SAS Inst. Inc., Cary, NC) using results from d 0 as independent covariates, and heifer as the experimental unit. Rumen pH on d 0 did not differ (P = 0.97) among treatments (7.197, 7.194, and 7.188 for HF, INT, and HG, respectively; SEM = 0.038). Ruminal pH on d 28 was greater (P ≤ 0.01) in HF compared with INT and HG (6.805, 6.628, and 6.380, respectively; SEM = 0.049), and greater (P < 0.01) in INT compared with HG. Vaginal and uterine pH on d 0 did not differ (P ≥ 0.24) among HF, INT, and HG (6.914, 6.965, 6.780 of vaginal pH, respectively, SEM = 0.082; 6.644, 6.760, 6, 592 of uterine pH, respectively, SEM = 0.079). Uterine and vaginal pH on d 28 also did not differ (P ≥ 0.64) among HF, INT, and HG heifers (6.926, 6.937, 6.918 of vaginal pH, respectively, SEM = 0.051; 6.567, 6.507, and 6.457 of uterine pH, respectively, SEM = 0.084). Therefore, dietary composition impacted rumen pH of beef heifers as expected, but without consequences to their vaginal and uterine pH.